Engineering Drawing Blueprint reading - Vogls Raymond; Siy, Louis J. ([S.l.] : Arco INC, 1981)
This hands-on, reader-friendly guide provides comprehensive, up-to-date coverage of welding symbols and their application to welding prints and practices. BLUEPRINT READING FOR WELDERS, Ninth Edition, uses step-by-step instructions and detailed illustrations to help you gain the knowledge and skills you need to interpret a wide range of working documents, from simple sketches to the most complex blueprints. The text covers auxiliary views, detail views, projections, sections, and detail and assembly drawings. Now updated and expanded, the new Ninth Edition features the latest AWS symbols and terms along with the ISO welding symbols,, current specifications and dimensioning practices, relevant industry developments, and cutting-edge information to support your professional success in this dynamic field.